Speed Matters: Relationship between Speed of Eye Movements and Modification of Aversive Autobiographical Memories - van Veen, Suzanne Chantal; van Schie, Kevin; Wijngaards-de Meij, Leoniek D. N. V.; Littel, Marianne; Engelhard, Iris M.; van den Hout, Marcel A. (Frontiers in Psychiatry, 2015)
Eye Movement Desensitization and Reprocessing (EMDR) is an efficacious treatment for posttraumatic stress disorder. In EMDR, patients recall a distressing memory and simultaneously make eye movements (EM). Both tasks are considered to require limited working memory (WM) resources. Because this leaves fewer resources available for memory retrieval, the memory should become less vivid and less emotional during future recall. Currently, EMDR is a standardized treatment and patients typically receive the same dual task manipulation of 1 EM cycle per second (1 Hz). From a WM perspective, the WM taxation of the dual task might be titrated to the WM taxation of the memory image. We hypothesized that highly vivid images are more affected by high WM taxation and less vivid images are more affected by low WM taxation. In study 1, 34 participants performed a reaction time task, and rated image vividness and difficulty of retrieving an image, during five speeds of EM and no EM. Both a high WM taxing frequency (fast EM; 1.2 Hz) and a low WM taxing EM frequency (slow EM; 0.8 Hz) were selected. In study 2, 72 participants recalled three highly vivid aversive autobiographical memory images (n=36) or three less vivid images (n=36) under each of three conditions: recall + fast EM, recall + slow EM or recall only. Multi-level modeling revealed a consistent pattern for all outcome measures: recall + fast EM led to less emotional, less vivid and more difficult to retrieve images than recall + slow EM and recall only, and the effects of recall + slow EM felt consistently in between the effects of recall + fast EM and recall only, but only differed significantly from recall + fast EM. Crucially, image vividness did not interact with condition on the decrease of emotionality over time, which was inconsistent with the prediction. Implications for understanding the mechanisms of action in memory modification and directions for future research are discussed.